2009
DOI: 10.1515/znc-2009-3-414
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Salicylic Acid in Arabidopsis Protects Plants against Moderate Salt Stress

Abstract: Previous studies showed that salicylic acid (SA)-defi cient transgenic Arabidopsis expressing the salicylate hydroxylase gene NahG had a higher tolerance to moderate salt stress. SA may potentiate the stress response of germination and growth of Arabidopsis seedlings by inducing reactive oxygen species (ROS). However, the detailed mechanism for a better adaption of NahG plants to moderate salt stress is largely unknown. In the present study we found that a higher GSH/GSSG (glutathione/oxidized glutathione) rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3
1

Relationship

3
7

Authors

Journals

citations
Cited by 75 publications
(39 citation statements)
references
References 33 publications
0
38
0
1
Order By: Relevance
“…tomato [Szepesi et al, 2009;Gémes et al, 2011] and Arabidopsis [Borsani et al, 2001;Cao et al, 2009]) indicated that the Agave species tested are resistant to this phytotoxic phenolic compound. Toxicity is believed to be associated with an extensive oxidative damage produced when SA is applied at relatively high (≥0.1 mM) concentrations (Rao et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…tomato [Szepesi et al, 2009;Gémes et al, 2011] and Arabidopsis [Borsani et al, 2001;Cao et al, 2009]) indicated that the Agave species tested are resistant to this phytotoxic phenolic compound. Toxicity is believed to be associated with an extensive oxidative damage produced when SA is applied at relatively high (≥0.1 mM) concentrations (Rao et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…• C for 20 min at 12,000 g and the resulting supernatant was used for the determination of the enzymatic activity (Zhu et al 2000;Cao et al 2009). …”
Section: Determination Of Photosynthetic and Respiratory Parametersmentioning
confidence: 99%
“…It suggests that higher ratios of GSH/GSSG and ASA/DHA may be the reason for symptom alleviation in SA-deWcient plants. SA-deWcient NahG plants are also insensitive to moderate abiotic stresses, which could be similarly attributed to their high ratios of GSH/GSSG and ASA/DHA (Borsani et al 2001;Yuan and Lin 2008;Cao et al 2009).…”
Section: Fig 4 Symptom and Virus Accumulation Of Cmv-infectedmentioning
confidence: 99%